2021
DOI: 10.1016/j.jmig.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Conversion to Open Surgery in Benign Gynecologic Laparoscopies: A Case-Control Study

Abstract: Study Objective: To describe cases of conversion from gynecologic laparoscopy to open surgery and to assess risk factors for conversion and conversion outcomes. Design: A retrospective case-control study. Setting: Tertiary referral hospital in Melbourne, Australia. Patients: Eighty-five cases of conversion from laparoscopy to laparotomy and 170 controls matched by age, surgical date, and gynecologic unit from 2006 to 2017. Interventions: Demographic, clinical, and surgical data were collected and compared betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(52 reference statements)
2
1
0
Order By: Relevance
“…The higher conversion rate was associated with a prolonged duration of the operation, and a longer hospital stay. These main ndings of our current study, notably factors for conversion, were consistent with the results of some but not all previous studies [3,11,12]. Twijnstra et al [5] reported in their prospective single-institutional analysis of 1534 patients a signi cant increase in conversion rates starting at a uterine weight of > 500gr (OR, 30.90; p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The higher conversion rate was associated with a prolonged duration of the operation, and a longer hospital stay. These main ndings of our current study, notably factors for conversion, were consistent with the results of some but not all previous studies [3,11,12]. Twijnstra et al [5] reported in their prospective single-institutional analysis of 1534 patients a signi cant increase in conversion rates starting at a uterine weight of > 500gr (OR, 30.90; p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…The increased risk for postoperative complications such as wound infections, necessary blood transfusions or repeat surgery which we saw in the converted group was also reported by other studies [3,10,12].…”
Section: Discussionsupporting
confidence: 87%
“…Single laparoscopic surgery instruments were used for the surgery. The surgical technique for the MPLS procedure conformed to that used by Richards et al ( 13 ). In addition, the pneumoperitoneum was maintained at 12 mmHg.…”
Section: Methodsmentioning
confidence: 99%